Commentary on Interictal epileptogenic zone localization in patients with focal epilepsy using electric source imaging and directed functional connectivity from low‐density EEG - Jehi, Lara (Epilepsia open, 2020)
ESI is a noninvasive technique that uses mathematical algorithms to localize the source of a given EEG pattern in real time, 2 while DFC refers to methods that appeal to temporal precedence of electrophysiology or imaging data to construct macroscopic neural networks and infer directed connectivity. 3 The classical study subject matter for both ESI and DFC has been high‐density EEG or iEEG. The authors selected 20 patients with temporal lobe epilepsy (TLE) and 14 with extratemporal lobe epilepsy (ETLE) who had a focal magnetic resonance imaging lesion, invasively well‐characterized presumed EZ, and ≥10 interictal epileptic discharges of the same (single) type on low‐density EEG. [...]the true significance of higher concordance in TLE vs ETLE cannot be judged given the fact that TLE resections were larger than those in ETLE, which by itself increases the likelihood of including an area of abnormal ESI measurements in the resection.